Informasi Anatomi Mri Knee Joint Sekuen T2 Space FS dan PD Space FS pada Potongan Sagital Dengan Klinis Ruptur Anterior Cruciate Ligament (ACL) - Arifina Nuridzati; Edy Susanto; Rasyid Rasyid (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: The T2 and PD sequences are the most sensitive sequences in evaluating injury to the ACL and surrounding soft tissue. Based on observations at the Radiology Installation of Dr. Sardjito Hospital Yogyakarta, the anatomical information generated in the MRI knee joint examination of the PD SPACE FS sequence is almost the same as the T2 SPACE FS sequence. The purpose of this study is to determine the differences in anatomical information and optimal sequences on MRI examination of the knee joint sagittal section sequences of PD SPACE FS and T2 SPACE FS in clinical ACL rupture.Method: This research was a quantitative study with an experimental approach, carried out at the Radiology Installation of Dr. Sardjito Hospital Yogyakarta on 10 samples with the application of different sequences for each sample, with the anatomy assessed by the informant namely ACL, meniscus, articular cartilage, and bone marrow. Further data analysis was carried out using the Wilcoxon test. Result: There was a difference in anatomical information between PD SPACE FS sequences and T2 SPACE FS sequences on MRI examination of the sagittal knee joint with clinical ACL rupture, with the ρ-value of the Wilcoxon test 0.001 or ρ-value0.05. This was due to differences in the use of TR and TE parameters in each sequence. The PD SPACE FS sequence was more optimal in visualizing anatomical information than the T2 SPACE FS sequence with an anatomical mean rank of meniscus 3.50, articular cartilage 3.50, and bone marrow 5.50, whereas in ACL anatomy the mean rank value was the same between the two sequences, which is 2.00. Conclusion: It was because the PD SPACE FS sequence had a more heterogeneous contrast difference than the T2 SPACE FS sequence so each anatomy could be well evaluated in the PD SPACE FS sequence.